Distribution of Gyrinops versteegii (Gilg.) Domke in varying vegetation structures, soil properties, and microclimates in Manggarai, Flores, East Nusa Tenggara - Titut Yulistyarini; Abban Putri Fiqa; Sugeng Budiharta; Ridesti Rindyastuti (Society for Indonesian Biodiversity, 2020)
Abstract. Yulistyarini T, Fiqa AP, Budiharta S, Rindyastuti R. 2020. Distribution of Gyrinops versteegii in varying vegetation structures, soil properties, and microclimates in western part of Flores Island, Indonesia. Biodiversitas 21: 1800-1808. Gyrinops versteegii is one of the agarwood-producing tropical plants that is distributed in the Lesser Sunda Islands to Sulawesi, Moluccas (Maluku), and Papua. The natural population of Gyrinops versteegii (Gilg.) Domke is widely exploited, making it being listed in CITES Appendix II. Despite largely exploited, information regarding the distribution of G. versteegii to reveal the habitat characteristics of its natural population is limited. The aims of the research were (i) to investigate the habitat characteristics of the distribution of G. versteegii in term of vegetation community, as well as soil and microclimate variables in its natural habitat in western part of Flores Island, and (ii) to study the relationship between its occurrence and ecological factors. The research was conducted in one community forest and three natural forests in the districts of Manggarai and West Manggarai, Flores Island, East Nusa Tenggara Province. Data on vegetation, soil properties and microclimates were collected by establishing 73 observation plots across the four studied areas. Data were analyzed to reveal vegetation composition and structure where G. versteegii occurred, the dispersion pattern, and relationship between its occurrence and ecological factors. Our study revealed that G. versteegii populations at four studied areas in Flores Island were distributed in a broad range of habitat characteristics with varying vegetation compositions and structures, canopy covers as well as soil and microclimates variables. The local/metapopulations of G. versteegii in these areas can be dispersed in clumped or uniform pattern. Nonetheless, some ecological variables might be important for the abundance of this species including soil texture, soil pH, C organic and Soil Organic Matters (SOM). The results of this study suggest a promising opportunity for the conservation efforts of G. versteegii through the possibility of planting this species in various land management including planted in monoculture system, polyculture system (e.g. home garden and agroforestry) as well as reintroduced into species-rich natural forest.